Implementation of the 5E Model Integrated STEM-EDP to Enhance High School Students' Creative Problem-Solving Ability - Ayida, Leovi Permata; Abdurrahman, Abdurrahman; Wicaksono, Blasius Anggit; Herlina, Kartini (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2025)
The improvement of Creative Problem-Solving (CPS) ability in physics learning still needs to be enhanced to prepare students for the challenges of the 21st century. This study aims to determine the effectiveness of implementing the 5E model integrated with STEM-EDP on high school students' CPS ability in the topic of Renewable Energy. This research was conducted at SMA Islam Global Surya using a quasi-experimental method with a pretest-posttest control group design. The sample consisted of class X-1 as the experimental group and class X-2 as the control group. The research instrument used was essay-type questions. The implementation of the 5E model integrated with STEM-EDP was found to be effective in improving students' Creative Problem-Solving ability. This is evident from the average N-Gain score of the experimental class, which was 0.56, higher than the control class with an average N-Gain score of 0.39. Additionally, this finding is supported by the results of the Independent Sample T-Test and Paired Sample T-Test, where the obtained Sig. (2-tailed) value was 0.00 < 0.05. Furthermore, the ANCOVA test results also showed a significance value of 0.00 < 0.05. The effectiveness of implementing the 5E model integrated with STEM-EDP in enhancing high school students' CPS ability in the topic of Renewable Energy falls into the high category, as indicated by the effect size test results, with a partial eta squared (η²) value of 0.434. This improvement is based on the Constructivism Theory and Behaviorism Theory, which allows students to build new knowledge by connecting it to prior experiences through interactions involving stimulus and response during the learning process.